Individual Analysis of Multidimensional Gender-based Poverty in Kepulauan Riau Province - Rahman, Dhia Fauzia; Rijanta, Raden; Mulyani, Wiwik Puji (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
Poverty has become a problem that always existed in various regions include Kepulauan Riau Province. This study aims to examine gender-based multidimensional poverty in Kepulauan Riau Province through the identification of the forming factors and the formulation of measurement results. Factor analysis used to analysis secondary data from susenas 2023. The result are factors that form the measurement of gender-based multidimensional poverty in Kepulauan Riau Province consist of access to information, housing and water resources, household status and assets, education and health. The women had lower conditions than men on almost all dimensions and indicators except for indicators of floor materials and residential status. Multidimensional poverty in an area can differ according to the analysis unit and age group. However, women's multidimensional poverty in general tends to be higher than men's multidimensional poverty.